Los nuevos colores de Mokey Fraggle - Paul, Emily; Di Fiori, Lawrence (Mexico : Sitesa, 1989)
As Mokey Fraggle creates an artistic masterpiece, she introduces a variety of colors.
Translation of: Mokey Fraggle's new colors.
Keywords: Color -- Fiction; Artists -- Fiction; Puppets -- Fiction; Spanish language materials